HAK WARGA NEGARA MEMPEROLEH PENDIDIKAN DAN JAMINAN PEMERINTAH MENYELENGGARAKAN PENDIDIKAN BAGI WARGA NEGARANYA - Alya Fitriana (PT. Habe Cendekia Utama, 2025)
Education is a fundamental human right that plays a vital role in a country's social, economic, and political development. This study aims to identify and further understand the state's obligations in fulfilling the right to basic education and in providing basic education. Thus, this research is expected to contribute to knowledge and practice in improving access to and the quality of basic education in Indonesia. This study uses descriptive qualitative methods to explore the role of education in Indonesia and the state's responsibility in ensuring basic education. Education plays a crucial role for citizens, especially for Indonesia's younger generation. Civic education, national education, and non-formal education all share the same goal: to develop good citizens who are useful to the nation.